PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PEMIDANAAN DALAM PERKARA KORUPSI PADA PUTUSAN NOMOR 51/Pid.Sus-TPK/2024/PN Jkt Pst - Laurencia Dian Flaviana Agatha; Bambang Santoso (Verstek, 2025)
This study aims to assess the appropriateness of using expert testimony as evidence in the proving corruption  cases,  specifically  in  verdict  Number  51/Pid.Sus-TPK/2024/PN  Jkt.  Pst.  This  research  is normative legal research and it is prescriptive in nature, with legal sources obtained from primary and secondary legal resources. The technique of collecting legal in this research is by means of literature study and legal materials are obtained and processed using the deductive syllogism method. The author analyzes Articles 2 and 3 of the Law on the Against of Corruption Crime as the major premise, with Verdict Number 51/Pid.SusTPK/2024/PN Jkt. Pst. as the minor premise.The results showed that the judge's considerations in imposing a criminal sentence are consistent with Article 183 of KUHAP. In their legal reasoning, the panel of judges based their decision on the evidence and exhibits  presented,  which  convinced  them,  coupled  with  the  absence  of  any  findings  of  the  criminal irresponsibility.